Proyecto piloto para la gestión del riesgo en el departamento de Recursos Humanos de la Municipalidad de San Carlos - Vargas-Castillo, Yeilyn Johanna (Instituto Tecnológico de Costa Rica, 2019)
The present work consists in the elaboration of a pilot project for risk management in the Department of Human Resources of the Municipalidad de San Carlos, with the purpose of improving in this aspect and at the same time complying with the requirements stipulated by the Department of Control Internal of the same municipality. This study arises from the need to manage risk in this department and guide this process to be applied in other departments of the municipality. On the other hand, the methodology established by Sistema Especifico de Valoración del Riesgo Institucional (SEVRI) was used to make the proposal, resulting in the identification of risks, risk analysis, risk assessment and risk treatment, internal to the department in study. Finally, the study will cover the definition of the context of the Department of Human Resources in the subject of risk, based on the guidelines issued by the Comptroller General of the Republic on this matter and at the same time improve the performance of employees and perform the functions properly, obtaining better results, for the benefit of the municipality.
Proyecto de graduación (Bachillerato Universitario en administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2019.
Keywords: Riesgos administrativos; Administración de empresas; Recursos Humanos; Municipalidades; Research Subject Categories::SOCIAL SCIENCES::Business and economics